3‐D imaging, illustration, and quantitation of enteric glial network in transparent human colon mucosa. Issue 5 (17th March 2013) - Liu, Y. A.; Chung, Y. C.; Pan, S. T.; Shen, M. Y.; Hou, Y. C.; Peng, S. J.; Pasricha, P. J.; Tang, S. C.
Abstract Background Enteric glia form a network in the intestinal mucosa and have been suggested to engage in multidirectional interactions with the epithelium, blood vessels, nerves, and immune system. However, due to the dispersed nature of the glial network, standard histology cannot provide a global view of the network architecture. We prepared transparent human colon mucosa for three‐dimensional (3‐D) confocal microscopy with S100B immunostaining to reveal the location‐dependent glial network for qualitative and quantitative analyses. Methods Full‐thickness human colons were acquired from colectomies performed for colorectal cancer. We targeted the mucosa away from the tumor site to characterize the glial network morphology. Optical clearing (use of immersion solution to reduce scattering) was applied to generate transparent specimens for deep‐tissue microscopy. Key Results Two features of the glial network were seen: (i) A dense glial population resides at the crypt base/mucosal boundary in contact with the lymphatic vessels, and (ii) from the base, the glial network elongates along the crypt axis with peri‐cryptic and peri‐vascular connections toward the opening. We quantified the mucosal glia as the S100B‐positive cells with at least two processes extending from the cell body. Examples of the global and in‐depth imaging of adenoma were given to illustrate the morphological correlation between the loss of glial fibers and the aberrant crypts. Conclusions & Inferences We have established a useful approach for 3‐D imaging, panoramic illustration, and quantitation of the enteric glia in the human colon mucosa to help characterize their roles with mucosal components in health and disease.